Low blood pyruvate levels and their association with chronic fatigue syndrome and BMI [Articol] - Râtea, Camelia (Editura USM, 2024)
The aim of this study was to investigate the relationship between low blood pyruvate levels, Chronic Fatigue Syndrome (CFS) and body mass index. We conducted a small study involving 31 patients diagnosed with CFS and overweight or obese, distribution between male and female are 28 women and 3 men. Blood samples were collected from all participants at Alfalab Chisinau, Pyruvate in plasma (pyruvic acid) using the NaF blood the analysis was performed at MDI Limbach Berlin GmbH MVZ Labor Limbach Berlin, Germany, normal reference range of 24-95 μmol/l. Other data were collected during nutritional consultations, at NUTHEIA EDUCATION SRL – Nutrition and Dietetics Center, Chisinau, such as the levels of BMI were recorded using Bioimpedance Scale. Other relevant measures, such as signs and symptoms of eating and digestive disorders reported by the patient, were also recorded during the nutritional assesment. The study found that patients with CFS had lower levels of blood pyruvate furthermore, there was a correlation between blood pyruvate levels and Body mass index. These findings suggest that low blood pyruvate levels are associated with CFS and may contribute to the pathophysiology of the syndrome. This study highlights the potential of blood pyruvate levels as a biomarker for diagnosing CFS and guiding nutritional treatment strategies in overweight and obese people.
Keywords: pyruvate; body mass index; chronic fatigue syndrome (CFS); poor nutrition; health